Sistem Informasi Absensi Siswa berbasis Website menggunakan Auto Generated QR Code - Pangki Pradana; Zulia Karini; Abednego Dwi Septiadi (Infoman's : Jurnal Ilmu-ilmu Manajemen dan Informatika, 2021)
The problem that occurs in the research entitled "Information System for Website-Based Student Attendance Information System Using Auto Generated QR Code (Case Study: SMK Bakti Purwokerto)" is that the attendance system currently running still applies the conventional system, namely by entering the attendance data from physical files into in digital files using the Microsoft Excel application. Then the difficulty of the teacher in carrying out attendance records is still inaccurate, because the picket officers only take the absent paper once a day in the morning during the first lesson. So that if there are students who skip school hours after attendance, they are still recorded as attending the teacher's recapitulation. The purpose of the research carried out by researchers was to build a website-based student attendance information system using an auto-generated QR Code at SMK Bakti Purwokerto in order to help school officers, especially for Student and Teachers, in the attendance process and recapitulation to be more accurate and efficient. The system development method used is the waterfall method using system design tools such as DFD and ERD. The results of this study are in the form of a website-based student attendance system using an auto-generated QR code, as for the calculation of the system testing using a Likert scale as a support to the questionnaire which shows the results of 84.14% in the very good category.